Ulterior lexical markers of sacredness in Boris Grebenschikov’s song lyrics (a linguoconceptual analysis) - Leszczak, Oleg; Robak, Michał (Przegląd Wschodnioeuropejski, 2023)
The study presented in this article is based on a corpus of 200 songs by a Russian poet and singer Boris Grebenschikov. The cognitive space of sacredness is one of the key spaces in the artistic discourse worldview of Boris Grebenschikov. The authors emphasize that the sacredness in the interpretation of the Russian poet does not relate to any specific religion. It is universal and mystical but, at the same time, it is emphasized anthropocentrically. The authors demonstrate the specifics of the poet's artistic depiction of sacred phenomena, physical objects and substances through explicit and implicit lexical nominations and descriptions. Descriptions of impossible or unknown spatial-temporal phenomena, events, and hidden knowledge are referred to as markers of the implicit representation of the sacred. The same goes with the names of especially important substances, e.g., salt, water, dust and unnatural phenomena. The linguoconceptual analysis of Grebenschikov’s idiostyle aimed at uncovering the cross-cutting motives and characteristics of the poet’s entire work is of a functional and pragmatic nature.